Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - Arena, C; Vitale, L; Virzo de Santo, A (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2008)
Abstract Photosynthesis and photoprotective mechanisms were investigated in the field on Laurus nobilis L. and Quercus ilex L. leaves exposed to summer drought (July) and winter cold (February) conditions compared with no-stress conditions (May). In July, net photosynthetic rate (A) and stomatal conductance (g s) decreased significantly compared with May in both species; conversely the highest ETR/A ratio and no difference in non-photochemical quenching (NPQ) was observed. In February A, g s and ETR/A declined compared with May but the highest NPQ were found in both species. Our data suggest that during summer, an increase of photochemical alternative pathways to carbon reduction, were able to effectively protect the photosynthetic apparatus under drought. In winter, the thermal dissipation of excess absorbed light constitutes the main safety valve for the photosynthetic apparatus.
doi: 10.1080/11263500802410819
Keywords: Dissipative processes; L. nobilis; leaf gas-exchange; Q. ilex; summer drought; winter cold

Photosynthetic response of Quercus ilex L. plants grown on compost and exposed to increasing photon flux densities and elevated CO 2 - Arena, C; Vitale, L; Santo, A Virzo De (Photosynthetica, 2005)
Quercus ilex plants grown on two different substrates, sand soil (C) and compost (CG), were exposed to photosynthetic photon flux densities (PPFD) at 390 and 800 µmol(CO2) mol -1 (C390 and C800). At C800 both C and CG plants showed a significant increase of net photosynthetic rate (PN) and electron transport rate (ETR) in response to PPFD increase as compared to C390. In addition, at C800 lower non-photochemical quenching (NPQ) values were observed. The differences between C390 and C800 were related to PPFD. The higher PN and ETR and the lower dissipative processes found in CG plants at both CO2 concentrations as compared to C plants suggest that substrate influences significantly photosynthetic response of Q. ilex plants. Moreover, short-term exposures at elevated CO2 decreased nitrate photo-assimilation in leaves independently from substrate of growth.
Keywords: chlorophyll fluorescence induction; electron transport rate; irradiance; nitrate; non-photochemical quenching; oak